2016
DOI: 10.1542/peds.2016-1813
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Autism Associated With Hyperbilirubinemia and Phototherapy

Abstract: OBJECTIVE: Whether neonatal hyperbilirubinemia and/or phototherapy increase the risk of autism spectrum disorder (ASD) is unclear. We sought to quantify the risk of ASD associated with elevated total serum bilirubin (TSB) levels and with phototherapy. METHODS:In a retrospective cohort study of 525 409 infants born at ≥35 weeks' gestation in 15 Kaiser Permanente Northern California (KPNC) hospitals, 1995-2011, we obtained all TSB levels and determined which infants received phototherapy. From the KPNC Autism Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 56 publications
2
20
0
1
Order By: Relevance
“…Neonatal jaundice and ASD were not associated in our adjusted model, despite research supporting the connection (8,14,28,30,34). The results mirror recent research, finding no association between ASD and hyperbilirubinemia identified by bilirubin laboratory values (40), and suggest that confounders have an impact on previous studies linking jaundice and ASD.…”
Section: Perinatal and Neonatal Factorssupporting
confidence: 66%
“…Neonatal jaundice and ASD were not associated in our adjusted model, despite research supporting the connection (8,14,28,30,34). The results mirror recent research, finding no association between ASD and hyperbilirubinemia identified by bilirubin laboratory values (40), and suggest that confounders have an impact on previous studies linking jaundice and ASD.…”
Section: Perinatal and Neonatal Factorssupporting
confidence: 66%
“…30,54 A growing number of studies are now exploring the risk of bilirubin-induced neurotoxicity in jaundiced infants based on unbound bilirubin rather than serum/plasma bilirubin. 37,53 Few studies have associated severe jaundice with epilepsy, 30,55 while the association with autism, [56][57][58][59] and childhood asthma [60][61][62] remains a subject of ongoing investigation and debate. In one rare longitudinal study in Finland, the authors investigated the long-term impact of severe hyperbilirubinaemia (TSB ≥20 mg/dL or 342 µmol/L) on educational, occupational and social functioning in a cohort (n=128 versus 82 controls) over a 30year period.…”
Section: Long-term Sequelaementioning
confidence: 99%
“…However, relevant research has resulted in inconsistent findings. Some studies demonstrated that neonatal jaundice increased the risk of ASD (12)(13)(14)(15)(16)(17)(18)27), whereas others did not (19)(20)(21). A recent population-based study objecting to investigate long-term neurodevelopmental outcomes of significant neonatal jaundice reported a 1.5 to 2-times greater risk for ASD than the reference cohort (28).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies exploring the relationship between the history of neonatal jaundice and ASD have produced conflicting results. While some studies have indicated that infants who developed neonatal jaundice are subsequently at risk of ASD (13)(14)(15)(16)(17)(18), others have failed to find any significant association (19)(20)(21). Moreover, limited research has focused mainly on the association between the history of neonatal jaundice and ASD.…”
Section: Introductionmentioning
confidence: 99%